The DOCTRINAL DIFFRENCE BETWEEN The MALIKIS And Al-DHAHERIYA In The BOOK Of SUPERVISING The JOKES Of DISPUTE ISSUES For ABDUL WAHAB Al-MALI;I (t422h) The DOOR Of FASTING As A MODEL COMPARATIVE JURISPRUDENCE (Islamic Sciences Journal, 2023)
Thank of Allah, thank of Allah, And peace and prayers for the Prophet Muhammad And on his god and friends who are worthy of praise and glory but afte This is a research presented to the Faculty of Islamic Sciences at Tikrit University entitled The doctrinal difference between The Malikis and al-Dhaheriya in the book of supervising the jokes of dispute issues for Abdul Wahab al-Maliki t422h the door of fasting as a model Comparative jurisprudence.The idea of the topic; To identify the issues in which the Malikis disagreed with al-Dhahiriya and study them on the four doctrines with al-Dhahiriya.Research Methodology: Inductive Approach.The aim of the study; is to highlight the importance of knowing the reasons for the differences of jurists and identifying their shortcomingsI have examined this through three demands:The first requirement: the introduction of the title terms and a profile of Judge Abdul Wahab al-Maliki.The second requirement is to differ in matters relating to the provisions of fasting and fasting of the traveller.Third requirement: differences in matters related to succession in the judiciary.The research was followed by a conclusion in which it mentioned its most important findings, including;1-The reasons for the difference between the fuqaha'a, but in general, do not differ from the understanding of a text or taking into account the custom or a linguistic interpretation and a meaning or a protest with evidence or knowledge of a modern.2-There is no difference in the real sense between the jurists in the origins of the issues but they differed in their branches.